ANALISA LAHAN DAN REKOMENDASI JENIS TANAMAN PADA PERTANIAN CERDAS BERBASIS IOT - Busran, Busran; Syahrani, Anna; Putra, Eko Kurniawanto; Yulianti, Eva; Djauhari, Muhammad vajri (ITP Press, 2024)
Technology-based agriculture is a modern approach that utilises the Internet of Things (IoT) to efficiently support the production process. In Kampung Durian Tarung, Pasar Ambacang, Kuranji, Padang, West Sumatra, a group of horticultural farmers face challenges in determining the type of plants that are suitable for the soil quality of their land. This research develops an IoT-based system for land analysis that can recommend optimal crop types according to soil conditions. IoT technology is implemented to collect soil data, such as pH, moisture, and soil temperature, through wireless sensors. The data is analysed using a fuzzy method, which enables decision-making based on a number of soil quality parameters to provide more precise and real-time recommendations. The trial results show that the system is able to accurately measure soil conditions and provide appropriate crop recommendations based on the soil quality data obtained. The use of fuzzy methods proved effective in filtering data from sensors and adjusting crop recommendations based on threshold values on pH, humidity, and soil temperature. This research contributes to the field of smart agriculture by presenting an IoT-based solution specific to the needs of local horticulture farmers. Combining wireless sensor technology and fuzzy methods enables analyses that are more adaptive and relevant to the soil conditions on the farm. The success of this research provides direction for the development of similar systems that can be applied in other regions, and underlines the role of IoT technology in supporting agricultural sustainability through optimal utilisation of data.